2009
DOI: 10.1103/physrevd.79.035003
|View full text |Cite
|
Sign up to set email alerts
|

Sneutrino as the lightest supersymmetric particle inB3minimal supergravity models and signals at the LHC

Abstract: We consider B 3 minimal supergravity models where we have one lepton number violating L i Q j " D k operator at the grand unification scale. This can alter the supersymmetric mass spectrum leading to a sneutrino as the lightest supersymmetric particle in a large region of parameter space. We take into account the restrictions from neutrino masses, the muon anomalous magnetic moment, b ! s, and other precision measurements. We furthermore investigate existing restrictions from direct searches at LEP, the Tevatr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…[12] studied the signature of same sign dilepton plus jets and missing energy from gluino-and squark-pair as well as the squark-gluino associated productions. Other relevant studies, some of which studied the previous signatures earlier, can be found in [22][23][24][25][26][27][28][29][30][31][32]. But these signatures are fairly model dependent thus not representative signatures of SUSY with a sneutrino LSP.…”
Section: Jhep10(2014)164mentioning
confidence: 99%
“…[12] studied the signature of same sign dilepton plus jets and missing energy from gluino-and squark-pair as well as the squark-gluino associated productions. Other relevant studies, some of which studied the previous signatures earlier, can be found in [22][23][24][25][26][27][28][29][30][31][32]. But these signatures are fairly model dependent thus not representative signatures of SUSY with a sneutrino LSP.…”
Section: Jhep10(2014)164mentioning
confidence: 99%
“…This issue can be resolved by imposing a Z 6 discrete symmetry, known as proton hexality (P 6 ), which leads to the same renormalizable superpotential as R-parity [11,12], but is incompatible with a GUT symmetry. Alternatively, one can impose a Z 3 -symmetry known as baryon-triality (B 3 ) [11,[13][14][15][16][17][18]. The latter allows for lepton number violating operators in the superpotential thanks to which the neutrinos acquire Majorana masses, without introducing a new very high energy Majorana mass scale [15][16][17][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In RPV SUSY, lepton number can be violated at tree level in interactions between fermions and sfermions, and theν τ may be the LSP [7]. For the resonantν τ signal, the following trilinear RPV part of the superpotential is considered:…”
Section: Introductionmentioning
confidence: 99%
“…In RPV SUSY, lepton number can be violated at tree level in interactions between fermions and sfermions, and the may be the LSP [ 7 ]. For the resonant signal, the following trilinear RPV part of the superpotential is considered: , where i , j , and are generation indices, L and Q are the doublet superfields of the leptons and quarks, and and are the singlet superfields of the charged leptons and down-like quarks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation